Efektivitas Formulasi Ekstrak Daun Sirih Merah (Piper crocatum) Dengan Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Terhadap Hiperglikemia Serta Histopatologi Pankreas Mencit: The Effectiveness of Formulation of Red Betel Leaf Extract (Piper crocatum) With Fragrant Pandan Leaf Extract (Pandanus amaryllifolius Roxb.) Against Hyperglycemia and Pancreatic Histopathology of Mice - Handini, Hesti Dwi; Rohmah, Jamilatur (Medicra (Journal of Medical Laboratory Science/Technology), 2018)
Diabetes mellitus (DM) is metabolism diseases characterized by hyperglycemia and change to the cell histophatology structure of pancreas. Red betel leaves (Piper crocatum) and fragnantpandanleaves (Pandanus amaryllifolius Roxb.) has compound metabolic secondary that efficacious as anantidiabetic. The aims of the study were seek the best extract formulations of red betel leaves (EDSM) and extract of fragnantpandan leaves (EDPW) to lowering blood glucose level, repair the damage of islet langerhans, and comparing the effectiveness with metformin. The research was drafted by post test only control group design using male mencit (Mus musculus) for 31 days. In this research used complete random design with 14 treatment groups, they are normal group, DM group, metfomin group, EDPW 100%group, EDSM 10%+ EDPW 90%group, EDSM 20% + EDPW 80%group, EDSM 30% + EDPW 70% group,EDSM 40% + EDPW 60% group,EDSM 50% + EDPW 50%group,EDSM 60% + EDPW 40% group,EDSM 70% + EDPW 30% group, EDSM 80% + EDPW 20% group, EDSM 90% + EDPW 10% group, and EDSM 100%group. Based on in vivo bioassay showed that metformin have a lot of lowering blood glucose levels (p<0,05) than formulation of EDSM and EDPW but not better in improving islet langerhans tissue damage and treatment DM group with EDSM 50% + EDPW 50% effective lowering blood glucose level comparable with metfomin (p>0,05) and better in improving islet langerhans tissue damage caused by alloxan diabetogenic compound.